Impact of Tourism Experience and Tourism Memory on the Revisit Intention: A Case Study of Tongling Grand Canyon Scenic Area, Jingxi City, China - Xu, Shijun; Leelapattana, Winitra; Tsai, Chin-Fa; Sitthikun, Suthira (Journal of Ecohumanism, 2024)
This study revolves around the Tongling Grand Canyon Scenic Area of Jingxi City, China, regarding the effect of tourism experience and travel memory on revisit intention. Due to its lesser popularity, China’s domestic tourism is not flourishing. Tongling Grand Canyon’s study tries to find the answer to the problem. With the help of the Stimulus-Organism-Response (SOR) model, this research examines how various dimensions of tourism experiences, particularly enjoyment, socialisation, participation, learning, relaxation, escape and challenge, will influence tourists’ desire to revisit. The moderating effect of travel memory on revisit intention is also explored. A cross-sectional survey was conducted among 411 subjects in Guangxi province. Results of multiple linear regression analysis indicate that as travel memory positively affects revisit intention, its most significant contributor is enjoyment and sociability. The results provide insights into how tourism managers should promote domestic tourist destinations by prioritising their enjoyment and sociability dynamics.